Feeling Better About Doing Worse Social Comparisons Within Romantic Relationships. [article]. - Lockwood, Penelope
The authors examined the role of closeness between self and partner in determining the impact of social comparisons within intimate relationships. To the extent that one's partner is a central aspect of one's identity, one maybe able to restore one's positive self-regard following an upward comparison with the partner by turning to the relationship as a self-affirmational resource. Studies 1 and 2 examined reactions to imagined comparisons; Studies 3 and 4 examined reactions to actual comparison feedback. Across studies, closeness moderated the impact of upward comparisons with the partner; that is, higher closenessparticipants responded to a more successful partner by focusing on their relationship-related strengths. However closeness did not moderate the impact of downward comparisons with the partner. -- (from the author)